Climate-induced range shifts of the American jackknife clam Ensis directus in Europe. - Raybaud, Virginie; Beaugrand, Gregory; Dewarumez, Jean; Luczak, Christophe (Biological Invasions, 2015)
International audience Mapping the future potential distribution of alien species has become an issue of great concern. Ecological niche models are increasingly used to forecast the spatial range of introduced species in the context of climate warming. Here, we studied the potential spread of the American jackknife clam Ensis directus into European waters. E. directus, a marine bivalve native to the American coasts, was observed in Europe for the first time in the German Bight at the end of the 1970s. Afterwards, the clam quickly colonized the surrounding waters of the North Sea. Although many studies focused on its biology, ecology and colonization, the extent to which E. directus may invade European and Nordic seas remained poorly known. In this study, we used two ecological niche models (ENMs), calibrated on the native area of the mollusk, to evaluate the potential distributional range of the bivalve over European seas. Under current environmental conditions, E. directus should continue to progress towards the southern coasts of France and may also invade new areas in the Adriatic Sea. Projections for the end of the century suggest that the probability of occurrence of E. directus increases from Denmark to France with both ENMs. The Tunisian coasts may also become a new suitable area for the mollusk but the results of the two ENMs differ for this region. Therefore, contrary to what is often observed, a southward range expansion of E. directus is probable, especially as climate will get warmer.